METODA SUBDOMENIILOR LA REZOLVAREA SISTEMELOR DE ECUAŢII INTEGRALE SINGULARE, DEFINITE PE CONTURURI NETEDE ÎNCHISE ÎN PLANUL COMPLEX - Capcelea, Maria; Capcelea, Titu (CEP USM, 2008)
It is proposed a calculation scheme of the sub-domain method for the approximate solving of systems of singular integral equations defined on simple closed and smooth contour in the complex plane. The theoretical justification of this method in the Hölder spaces scale is obtained.
Keywords: ecuaţii integrale singulare; spaţii Hölder; metoda subdomeniilor